SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS PADA AGUNG JAYA BERBASIS DESKTOP - Ridwanullah, Muhammad Jidan; Bokings, Tri Pratiwi Olivia Riska (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2025)
This research aims to analyze, design, implement and test the cash receipt and expenditure information system to facilitate the company's operational activities. The development method used is Waterfall with research instruments including observation, interviews, documentation, and literature studies. The analysis method used is PIECES. The results of the design of the cash receipt and expenditure information system are in the form of proof of cash inflow, proof of cash outflow, cash receipt report, cash expenditure report, and cash receipt and expenditure report. This system can process data on cash receipts and expenditures from data entry to report creation.